2006
DOI: 10.1002/lsm.20448
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐induced thermotherapy (LITT) elevates mRNA expression of connective tissue growth factor (CTGF) associated with reduced tumor growth of liver metastases compared to hepatic resection

Abstract: Background and Objectives: Proliferation and synthesis of hepatocellular tissue after tissue damage are promoted by specific growth factors such as hepatic tissue growth factor (HGF) and connective growth factor (CTGF). Laser-induced thermotherapy (LITT) for the treatment of liver metastases is deemed to be a parenchyma-saving procedure compared to hepatic resection. The aim of this study was to compare the impact of LITT and hepatic resection on intrahepatic residual tumor tissue and expression levels of mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…did not present baseline GF levels (day 0) that may also have shown a temporal decrease, as in our study. In agreement with our study, these two studies 26,27 reported decreased expression of particular GFs following TA, with an increase in HGF common to all three studies. We demonstrated a similar decrease in GF expression in the sham‐ablated controls, suggesting that the decrease most likely reflects a general effect of laparotomy rather than TA.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…did not present baseline GF levels (day 0) that may also have shown a temporal decrease, as in our study. In agreement with our study, these two studies 26,27 reported decreased expression of particular GFs following TA, with an increase in HGF common to all three studies. We demonstrated a similar decrease in GF expression in the sham‐ablated controls, suggesting that the decrease most likely reflects a general effect of laparotomy rather than TA.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, no difference emerged between TA‐treated animals and sham‐ablated controls at this time‐point, which is in agreement with our findings. Isbert et al 27 . did not present baseline GF levels (day 0) that may also have shown a temporal decrease, as in our study.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations